Survival analysis for clinical studies - Langová, Kateřina (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2008)
Aim: This paper focuses on the use of censored data in survival analysis. Survival analysis is used most frequentlyin the case of cancer patients when the study is fi nished and a number of individuals are still alive. The original articlecited2 was declared recently to be the most cited statistical study in the biomedical area. The goal of this paper is toexplain the basic principles and methods involved. The way survival analysis processes data and interprets outputs ispresented using the clinical data of oncological patients.Methods and Results: Survival analysis is used to estimate survivor function from survival data, to compare survivorfunctions and to assess the relationship of explanatory variables to survival time. These methods were applied to thedata of 176 patients with heamato-oncological diagnoses who had undergone bone marrow blood transplant.Conclusion: It is very important to use appropriate methods when processing statistical data. Standard statisticalprocedures used for incomplete data could not provide the correct estimation.
Keywords: lidé; Financing, Organized; lékařská onkologie; interpretace statistických dat; financování organizované; Medical Oncology; Survival Analysis; statistika jako téma; Data Interpretation, Statistical; hematologické nádory; analýza přežití; Humans; sběr dat; Data Collection; Statistics as Topic; Hematologic Neoplasms; Kaplanův-Meierův odhad; Proportional Hazards Models; Kaplan-Meier Estimate; proporcionální rizikové modely